Adaptive management of natural resources—framework and issues - Williams, Byron K. (Journal of Environmental Management)
Adaptive management, an approach for simultaneously managing and learn ing about natural resources, has been around for several decades. Inte rest in adaptive decision making has grown steadily over that time, an d by now many in natural resources conservation claim that adaptive ma nagement is the approach they use in meeting their resource management responsibilities. Yet there remains considerable ambiguity about what adaptive management actually is, and how it is to be implemented by p ractitioners. The objective of this paper is to present a framework an d conditions for adaptive decision making, and discuss some important challenges in its application. Adaptive management is described as a t wo-phase process of deliberative and iterative phases, which are imple mented sequentially over the timeframe of an application. Key elements , processes, and issues in adaptive decision making are highlighted in terms of this framework. Special emphasis is given to the question of geographic scale, the difficulties presented by non-stationarity, and organizational challenges in implementing adaptive management.